Comparison of ezetimibe and atorvastatin versus atorvastatin alone on short-term major adverse cardiac events after percutaneous coronary intervention, a double-blind placebo-controlled randomized clinical trial - Hossein Farshidi; Badri Bijani; Seyed Alireza Sobhani; Farideh Dastsouz; Shahin Abbaszadeh (Trials)
Abstract Background Major cardiovascular events (MACE) after percutaneous coronary intervention (PCI) are among the most common causes of death in patients. Lipid-lowering strategies seem to affect these events. Reaching the best regimen for controlling lipid abnormalities is important. This study aimed to compare the effect of ezetimibe and atorvastatin versus atorvastatin alone in short-term major cardiovascular events in patients after PCI in Bandar Abbas in 2018. Methods This double-blinded randomized controlled trial was done in Bandar Abbas in 2018 on 224 patients. Patients were randomly divided into two groups either to receive ezetimibe and atorvastatin (group A) or atorvastatin alone (group B). Patients were followed for 1 month for major cardiovascular events and drug side effects. Data was analyzed using SPSS software. Results Patients in the two groups had similar baseline characteristics. The mean low-density lipoproteins (LDL) level was 69.83 ± 28.8 in group A and 82.45 ± 29.9 in group B (P = 0.014). At the end of the study, high-sensitivity C-reactive protein (hs-CRP) values were notably lower in group A (P value = 0.005). Three (2.7%) patients in group A and 1 patient (0.9%) in group B had a myocardial infarction (P value = 0.313). Also, 11 patients (9.8%) in group A and 13 patients (11.6%) in group B had unstable angina (P value = 0.666). No patients had death, cerebrovascular event, or stent thrombosis in the two groups. Conclusion Although adding ezetimibe to atorvastatin can decrease LDL and hs-CRP levels in short-term follow-up; it is not effective in lowering short-term major cardiovascular events in patients after PCI. Studies with longer-term follow-up are recommended. Trial registration IRCT, IRCT20171028037047N1. Registered on 22 June 2018, https://irct.behdasht.gov.ir/trial/28808 .